‘Psychopaths’ at Work? Implications of Lay Persons’ Use of Labels and Behavioural Criteria for Psychopathy - Caponecchia, Carlo; Sun, Andrew Y. Z.; Wyatt, Anne (2012)
In attempting to explain or deal with negative workplace behaviours such as workplace bullying, the notion of ‘workplace psychopaths’ has recently received much attention. Focusing on individual aspects of negative workplace behaviour is at odds with more systemic approaches that recognise the contribution of individual, organisational and societal influences, without seeking to blame a person(s) for their behaviour or personality disorder. Regarding a coworker as a psychopath is highly stigmatising, and given the relatively low prevalence of psychopathy in the community, is likely to be incorrect. Sources promoting the notion of workplace psychopathy provide lists of diagnostic criteria and appear to encourage the perception that it is common. This research examines how lay persons use behavioural criteria consistent with psychopathy and the label ‘psychopath’ in relation to a coworker. 307 Australian workers completed an online survey concerning their experience of workplace bullying, which also asked them to rate a coworker’s behaviour on a range of scales to assess perceptions of psychopathy. Rates of psychopathy, when using labels and behavioural criteria, were found to be much higher than scientific estimates of prevalence, for both participants who had been bullied and those who had not. A higher proportion of non-bullied participants classified a coworker as a psychopath when using the label ‘psychopath’, compared to when using behavioural criteria. The notion that there are psychopaths in every workplace should be treated with caution to ensure that the potential for ‘misdiagnosis’ and stigmatisation do not cause further harm in situations of unacceptable workplace behaviours.
Keywords: Prevalence; Mis-diagnosis; Stigmatisation; Workplace bullying; Psychopathy